Family acceptance, economic situation, and faith community: The lived experiences of ex-convicts in Ghana - Elijah Tukwariba Yin; William Boateng; Nelson Kofie (Social Sciences and Humanities Open, 2022)
Most ex-convicts re-offend at some point in their post-imprisonment lives. The literature reveals mixed findings on the relationship between ex-convicts’ reintegration and family embrace, employment opportunities, and Faith Community Organizations (FCOs). This paper examines the lived experiences of ex-convicts in respect of family support, economic situation, and the extent to which their faith communities related to them. The study approach was purely qualitative, with phenomenology as the research design. The data collection method was the use of interviews. The unit of analysis included 10 - ex-convicts, 1 - prison chaplain, 2 - visiting clergy, and 5 - relatives of ex-convicts. These participants were purposively selected. The data was analysed based on themes and patterns. The analysed data revealed that ex-convicts’ hopeful expectations to be contributing members of society turned to frustration and disappointment. It was also found that most ex-convicts could not secure jobs due to their blemished character. The FCOs that visited prisons to proselytize to inmates rejected them upon discharge. The few FCOs that accepted ex-convicts into their family and church became victims of their criminal engagements. Although covert, the mark of disgrace for having been to prison, along with the stereotypes of what being in prison might have done to the individual, and the disassociation FCOs maintained with the ex-convicts intensified their woes. With the prevailing challenges, there is the need for institutional change, policy development and implementation to address the current problems in a systemic way.